Incomes and Expenditures of Ukrainian Households from 2015 till Earlier Half of 2016 - A. P. Revenko (Статистика України, 2016)
Principles of organization and practice of the surveys devoted to living conditions of households, conducted by the State Statistics Service of Ukraine, are studied. Change in the households’ incomes and expenditures from 2015 till earlier half of 2016 and the impact of inflation on them is analyzed. Consumption of basic foods by the population and self-assessment of material condition by the households is shown.